Enron and the Use and Abuse of Special Purpose Entities in Corporate Structures - Schwarcz, Steven L. (Senate Hall Academic Publishing, 2005)
This essay examines what, if anything, differentiates Enron’s questionable use of offbalance-sheet special purpose entities, or SPEs, from the trillions of dollars of supposedly “legitimate” securitization and other structured finance transactions that use SPEs. The inquiry is important because the absence of meaningful differences would call all these transactions into question, whereas the presence of meaningful differences may inform regulatory schemes by providing a basis to distinguish which structured finance transactions should be allowed. This essay also introduces the dilemma that some structured finance transactions are so complex that disclosure to investors in the sponsoring company is necessarily imperfect – either oversimplifying the transactions, or providing detail and sophistication beyond the level of most investors. The essay argues that the company’s investors must rely, to some extent, on the business judgment of management in setting up these structures for the company’s benefit.
Keywords: securitization; structured finance; Enron; special purpose entity; off-balance sheet; SPE